Should the Individual Voting Records of Central Bankers be Published? - Volker Hahn; Hans Gersbach (Deutsche Bundesbank, 2001)
We examine whether it is socially beneficial for the individual voting records of central bank council members to be published when the general public is unsure about central bankers' efficiency and central bankers are aiming for re-election. We show that publication is initially harmful since somewhat less efficient central bankers attempt to imitate highly efficient central bankers in their bid to get re-elected. After re-election, however, losses will be lower when voting records are published since the government is more easily able to distinguish highly efficient from less efficient central bankers and can make central bankers individually accountable. Nevertheless, the negative effects of voting transparency predominate and expected overall losses are always larger when voting records are published. – – Wir untersuchen, ob die Veröffentlichung über das individuelle Abstimmungsverhalten von Zentralbankratsmitgliedern gesamtwirtschaftlich nützlich ist, wenn in der Öffentlichkeit Unsicherheit über die Effizienz von Mitgliedern des Zentralbankrats besteht und sich diese um eine Wiederwahl bemühen. Wir weisen nach, dass eine Veröffentlichung zunächst Schaden anrichtet, weil etwas weniger effiziente Mitglieder des Zentralbankrats versuchen, hocheffiziente Zentralbankratsmitglieder in ihren Bemühungen um eine Wiederwahl nachzuahmen. Nach der Wiederwahl sind die Verluste aber geringer, wenn die Abstimmung veröffentlicht wird, weil die Regierung hocheffiziente von weniger effizienten Zentralbankratsmitgliedern leichter unterscheiden und sie einzeln zur Rechenschaft ziehen kann. Die negativen Auswirkungen einer Transparenz des Abstimmungsverhaltens überwiegen aber, und die Nachteile sind insgesamt immer größer, wenn die Abstimmung veröffentlicht wird.
Keywords: 330; Zentralbank; Abstimmung; Publizitätspflicht; Geldpolitik; Public Choice; Wohlfahrtseffekt; Soziale Kosten; Theorie